Design of anomalous reflecting metasurface for communication systems - Hany M. Zamel; Eman M. Eldesouki; Ahmed M. Attiya (Scientific Reports)
Abstract This paper presents a novel design approach for an anomalous reflector metasurface for communication systems operating at 8 GHz band. The main contribution of this work is the development of a general analytical method that accurately calculates the electromagnetic response of realistic metasurfaces with periodic impedance profiles. The modulated surface impedance is achieved by incorporating appropriately sized conductive patches on a grounded dielectric substrate. The proposed design utilizes a genetic algorithm (GA) optimization technique to optimize the surface impedance that achieving efficient reflection of incident waves towards a specific angle of 45˚. The optimization process targets a specific impedance profile derived from the analytical model, leading to the desired anomalous reflection behavior. Then by using periodic boundary conditions, dimensions of an elliptical unit cells can be obtained. To evaluate the anomalous reflection performance, the bistatic radar cross section (BRCS) are simulated at different frequencies. A reflector metasurface sheet is fabricated and measured for verification. The proposed approach provides a foundation for implementing intelligent metasurfaces in various communication applications.